Readings in the sociology of religion - Brothers, Joan, 1938- (Commonwealth and international library of science, technology, engineering and liberal studies. Readings in sociology., 1967)
Readings in the Sociology of Religion is a collection of articles that examines the sociological aspects of religion. The title discusses the contemporary theories, concept, and studies about the sociology of religion. The text first details the concept of sociology of religion, along with the relationship between religion and sociological theory. Next, the selection covers the theoretical development of the sociology of religion and Weber's sociological theory, as well as the modern dilemma of value and belief in the social sciences. The last part tackles the types of research in sociology of.